2020
DOI: 10.1038/s41413-020-00118-w
|View full text |Cite
|
Sign up to set email alerts
|

Evading the host response: Staphylococcus “hiding” in cortical bone canalicular system causes increased bacterial burden

Abstract: Extremity reconstruction surgery is increasingly performed rather than amputation for patients with large-segment pathologic bone loss. Debate persists as to the optimal void filler for this “limb salvage” surgery, whether metal or allograft bone. Clinicians focus on optimizing important functional gains for patients, and the risk of devastating implant infection has been thought to be similar regardless of implant material. Recent insights into infection pathophysiology are challenging this equipoise, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 64 publications
(105 reference statements)
0
23
0
4
Order By: Relevance
“…are also present in PJI, which could be linked to biofilm formation. Intracellular internalization of staphylococci, particularly “Small colony variant” strains, besides invasion and colonization of the lacuna-canalicular system of cortical bone are other causes of PJIs ( Parvizi et al, 2013 ; Zoller et al, 2020 ). A clinical study explored if ASA could promote infection control for patients with periprosthetic joint infections (PJIs) ( Wei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…are also present in PJI, which could be linked to biofilm formation. Intracellular internalization of staphylococci, particularly “Small colony variant” strains, besides invasion and colonization of the lacuna-canalicular system of cortical bone are other causes of PJIs ( Parvizi et al, 2013 ; Zoller et al, 2020 ). A clinical study explored if ASA could promote infection control for patients with periprosthetic joint infections (PJIs) ( Wei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of S. aureus colonization of the osteocyte lacuno canalicular network (OLCN) of live bone via transmission electron microscopy (TEM) analyses of infected bone from mice, and bone biopsies from patients with chronic osteomyelitis, has provided new insights into the problems of antibiotic therapy to treat bone infections [ 16 , 17 , 18 , 19 ]. Specifically, S. aureus within the OLCN is a permanent reservoir of bacteria that cannot be eradicated by host responses or any known treatments short of amputation [ 9 , 20 , 21 , 22 ]. While in vivo bromodeoxyuridine labeling studies in mice have demonstrated that orally administered small molecules have access to S. aureus at the leading edge of the colony within the OLCN [ 17 ], we have also shown that both methicillin-sensitive S. aureus (MSSA) [ 23 ] and methicillin-resistant S. aureus (MRSA) [ 24 ] OLCN invasion cannot be prevented or eradicated by combined high-dose local and systemic antibiotics, likely due to its well-known adaptive responses that are associated with persister cells and small colony variants (SCVs) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This submicron-scale invasion of bone permits S. aureus long-term survival and evasion of immune cell attack. Despite the challenges associated with identifying S. aureus bacterial cells deep within the infected bone, like finding a needle in a haystack, additional studies in models of fracture-related infection and implant-associated infection have been able to corroborate this novel mode of persistence (Alder et al, 2020;Zoller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%